Disentangling Managerial Incentives from a Dynamic Perspective: The Role of Stock Grants - Amal Hili; Didier Laussel; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the optimal contract between a risk-averse manager and the initial shareholders in a two-period model where the manager.s investment effort, carried out in period 1, and her current effort, carried out in period 2, both impact the second-period profit, so that it may be difficult to disentangle the incentives for these two types of effort. The contract stipulates (a) the profit-contingent cash remuneration for each period, (b) the number of shares that will be granted to the manager at the end of the first period and (c) the restrictions (if any) on the sales of the granted stock. We show that stock grants play different roles according to whether the signal of investment effort is less noisy, or noisier, than that of current effort. In the former case, at the optimal solution, the firm gives more incentive to investment effort than to period 2 current effort, and there is no need to restrict the sales of granted stocks: the stock grants then serve as an incentive device for investment effort, and it is efficient to permit the manager to sell all her shares to eliminate her dividend risks. In the latter case, the efficient contract does not allow the manager to sell her granted stock, and both current and investment efforts are given the same incentive. In this case, stock grants play a different role: they serve as commitment device to overcome the time-inconsistency problem. We determine simultaneously the optimal stock grants and the optimal restrictions on sales of shares.
Keywords: M51; M52; 330; stock grants; executive compensation; incentive contracts; moral hazard; agency problems